Managing Harmony Through Dialogue: Religious Leaders as Community Educational Managers - Dafina Fatana (Universitas Nurul Jadid, 2026)
Educational management scholarship has long assumed that effective pluralism education requires formal institutional infrastructure. Communities that sustain sophisticated tolerance education systems entirely outside formal organizational boundaries, however, challenge this assumption in ways the field has not adequately theorized. This study examines how Islamic and Hindu religious leaders exercise community-based educational management in sustaining inter-religious harmony within a multi-religious community whose unbroken record of coexistence across its entire settlement history constitutes an empirically distinctive case for educational management inquiry. Employing a qualitative phenomenological case study design, data were collected through semi-structured in-depth interviews, participatory observation, and documentary analysis, and were analyzed using an interactive qualitative data analysis model. The findings reveal three interdependent educational management strategies deployed by Tuan Guru and Parisade as community educational leaders: preventive program management through structured musyawarah dialogue, participatory experiential learning facilitation through gotong royong, and consensual curriculum governance through the Tri Mandala boundary framework, sustained by three enabling conditions of leader legitimacy, multi-channel communication competence, and sociocultural institutional memory. The implications for educational management are threefold: this study reconceptualizes educational management as a function exercisable across formal and non-formal boundaries, introduces sociocultural institutional memory as a generative theoretical construct for understanding community educational leadership continuity, and offers an empirically grounded model of pluralism education management directly applicable to SDG 4 and SDG 16 policy agendas in religiously diverse societies globally.